The Importance of Purchasing Decisions in E-Marketing Relationships and Online Store Customer Satisfaction - Akbar, Rizqi Maulana Ilhan; Suryaningsih, Ika Barokah; Susanto, Arnis Budi; Handriyono, Handriyono (Image : Jurnal Riset Manajemen, 2024)
The purpose of this research is to examine and analyze the important role of purchasing decisions in mediating the relationship between e-marketing and customer satisfaction. The sample used was 120 customers from Denpro Dental Store in Online Stores (Shopee and Tokopedia). The research uses a quantitative approach with the help of SmartPLS. The research results show that e-marketing in the form of convenience, responsiveness, marketing content, and trust plays an important role in increasing purchasing decisions. Purchasing decisions have an important impact on increasing customer satisfaction. An important implication of this research is that effective e-marketing strategies in the aspects of convenience, responsiveness, marketing content, and trust significantly increase purchasing decisions, which in turn increases customer satisfaction. Therefore, online stores like Denpro Dental Store must focus on improving the quality of their e-marketing to encourage positive purchasing decisions and increase customer satisfaction levels.